How do you solve (x - 2) ^ { 2} + 3= 4(x−2)2+3=4?
2 Answers
Apr 28, 2018
Explanation:
first expand the quadratic equation
then sum all the unknown and the constant which will give you
then factorise the equation and u get
therefore
Apr 28, 2018
Explanation:
"isolate "(x-2)^2" by subtracting 3 from both sides"isolate (x−2)2 by subtracting 3 from both sides
rArr(x-2)^2=4-3=1⇒(x−2)2=4−3=1
color(blue)"take the square root of both sides"take the square root of both sides
sqrt((x-2)^2)=+-sqrt1larrcolor(blue)"note plus or minus"√(x−2)2=±√1←note plus or minus
rArrx-2=+-1⇒x−2=±1
"add 2 to both sides"add 2 to both sides
rArrx=2+-1⇒x=2±1
rArrx=2-1" or "x=2+1⇒x=2−1 or x=2+1
rArrx=1" or "x=3⇒x=1 or x=3